2019
DOI: 10.1111/codi.14898
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of permanent stoma creation in patients with mid or low rectal cancer: results of a multicentre cohort study with preoperative evaluation of anal function

Abstract: Aim Preoperative factors predictive of permanent stoma creation were investigated in a long‐term follow‐up of patients with mid or low rectal cancer. Method We included patients who underwent radical resection for mid or low rectal cancer with available data for preoperative anal function measured by manometry and Faecal Incontinence Severity Index questionnaire between January 2005 and December 2015 in three tertiary referral hospitals. A permanent stoma was defined as a stoma present until the patient’s last… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 35 publications
0
12
0
1
Order By: Relevance
“…It is important to note, however, that the confidence intervals are still quite wide in most instances, reflecting the inherent difficulty in predicting a permanent stoma outcome from registry-based data alone. Clinicians and patients should interpret the results cautiously, keeping in mind in particular that some predictors, unmeasured in this study, might increase the stoma risk even further, such as alcohol and smoking abuse 25 , low socioeconomic status 26 , and an inflammatory state 23,24 . Further predictive research should include other factors of potential importance that are known before operation.…”
Section: Discussionmentioning
confidence: 96%
“…It is important to note, however, that the confidence intervals are still quite wide in most instances, reflecting the inherent difficulty in predicting a permanent stoma outcome from registry-based data alone. Clinicians and patients should interpret the results cautiously, keeping in mind in particular that some predictors, unmeasured in this study, might increase the stoma risk even further, such as alcohol and smoking abuse 25 , low socioeconomic status 26 , and an inflammatory state 23,24 . Further predictive research should include other factors of potential importance that are known before operation.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, studies of colorectal cancer might suggest some factors that could affect decision-making when ovarian cancer is involved. For example, the distance from the tumor to the anal verge was associated with the AL rate and survival outcomes of colon cancer; this has been proven but is not usually considered an indication by physicians treating ovarian cancer ( 23 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, PS developed in 58/278 (20.86%) patients with rectal cancer, which included 54 patients in whom stoma was created during initial surgery and four patients who underwent re-stoma after stoma reversal. Postoperative AL was a common and severe complication in patients with rectal cancer, especially low and ultra-low rectal cancer, causing poor postoperative recovery, longer hospital stays, anorectal dysfunction, and even death (17). It has been reported that tumor recurrence and AL were common independent risk factors for PS (12).…”
Section: Discussionmentioning
confidence: 99%
“…The continued existence of stoma may alter bowel habits, and could ultimately led to stoma-related complications including stoma hernia, stoma bleeding, stoma prolapse, dehydration, and electrolyte disorders (14,15). Numerous studies (4,8,(16)(17)(18) investigating the risk factors for PS have found that comorbidities, surgical complications, and tumor recurrence were commonly associated with PS (17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation